Corotating dyonic binary black holes - Cabrera Munguia, Roberto Ivan (2020)
This paper is dedicated to derive and study binary systems of identical corotating dyonic black holes separated by a massless strut—two 5-parametric corotating binary black hole models endowed with both electric and magnetic charges—where the dyonic black holes carrying equal/opposite electromagnetic charges in the first/second model satisfy the extended Smarr formula for the mass including the magnetic charge as a fourth conserved parameter.